0
$\begingroup$

Let $A_n$ be a sequence of events in probability space.

The event $A(i.o.)$=$\{A_n$ happens infinitely often $\}$ is formally stated as $\lim \sup A_n$ (in other words $\cap_{k=1}^\infty \cup_{n=k}^\infty A_n$).

This is because if an element belongs to $\lim \sup A_n$, it can be shown that it belongs to infinitely many $A_n$ (because it belongs to all sets $\cup_{n=k}^\infty A_n$).

In the proof of Borel-Cantelli lemma on page 2, it says:

$P(A(i.o.)) = \lim_{k \to \infty}P(\cup_{n=k}^\infty A_n)$.

According to the definition above, it's exactly the same as

$$P(\cap_{k=1}^\infty \cup_{n=k}^\infty A_n)= \lim_{k \to \infty}P(\cup_{n=k}^\infty A_n)$$

Could anyone prove this equality?

$\endgroup$
  • 2
    $\begingroup$ Note the sets $\bigcup_{n=k}^\infty A_n$ (for $k=1,2,\ldots$) form a decreasing chain. $\endgroup$ – Blackbird Dec 21 '15 at 18:02
1
$\begingroup$

Suppose that $B_1,B_2,\dots$ are a decreasing sequence of events. Then

$$ P\left(\bigcap_{n\ge 1} B_n\right) = \lim_{n\to\infty} P(B_n) $$

To see this define $E_{n}=B_1 \setminus B_n$. $E_n$ are measurable (i.e events) so we can assign them probability. Note also since $B_n$ is decreasing $E_n$ is increasing. We then have $ B_1=E_n \cup B_n $

and as $E_n$ and $B_n$ are disjoint

$$ P(B_1)=P(E_n)+P(B_n) \implies P(E_n)=P(B_1)-P(B_n) $$

By De Morgan's Law we also have $\bigcup E_n = B_1\setminus \bigcap B_n$. Therefore we have

$$ P\left(\bigcup E_n\right) = P(B_1)-P\left(\bigcap B_n \right) $$

Since $E_n$ is increasing, we have $P\left(\bigcup E_n \right)=\lim_{n\to\infty} P(E_n)$ (I entrust you to show this since it's a little easier, use the same technique - write the union as union of disjoint events)

Therefore

\begin{align*} P(B_1)-P\left(\bigcap B_n \right)&=\lim_{n\to\infty} P(E_n)\\ &=\lim_{n\to\infty} (P(B_1) - P(B_n))\\ &=P(B_1)-\lim_{n\to\infty} P(B_n) \end{align*}

(This result is standard for any measure space, as long as we are given that measure of the set $B_1$ is finite. But in probability space this is true for any event $B_1$)

Now apply this result to $B_k=\bigcup_{n\ge k} A_n$

$\endgroup$
-1
$\begingroup$

The equality follows by the continuity of probability $(*)$. See here for a proof of BCL1 and half of the continuity of probability.

$(*)$ If events $B_1, B_2, ...$ increase or decrease to some event $B$, then the $P(B_n)$'s increase or decrease, respectively, to $P(B)$.

In this case we have decreasing events $B_1, B_2, ...$ given by $B_k = \bigcup_{n=k}^{\infty} A_k$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.